A new variety of Bauhinia bassacensis (Leguminosae: Caesalpinioideae) from Great Nicobar Island, India - Tiwari, Umeshkumar; K., Ravikumar; N., Balachandran (Phytotaxa, 2013)
Bauhinia bassacensis var. nicobarica, described here as a new variety from Great Nicobar Island, India. Diagnostic characters for the variety nicobarensis include exstipulate leaves and obtuse lobes of leaflets, bracts ovate rusty tomentose, corolla deltoid and blade margin undulating and pods rusty tomentose. A comparative table with diagnostic morphological features to distinguish between the following three varieties of Bauhinia bassacensis: var. bassacensis var. backeri and var. nicobarica is provided. A detailed description with nomenclature, distribution, photographs and an illustration of the species is also provided.